Multisensory Training Improves Auditory Spatial Processing following Bilateral Cochlear Implantation - Isaiah, Amal (Society for Neuroscience, 2014)
Cochlear implants (CIs) partially restore hearing to the deaf by directly stimulating the inner ear. In individuals fitted with CIs, lack of auditory experience due to loss of hearing before language acquisition can adversely impact outcomes. For example, adults with early-onset hearing loss generally do not integrate inputs from both ears effectively when fitted with bilateral CIs (BiCIs). Here, we used an animal model to investigate the effects of long-term deafness on auditory localization with BiCIs and approaches for promoting the use of binaural spatial cues. Ferrets were deafened either at the age of hearing onset or as adults. All animals were implanted in adulthood, either unilaterally or bilaterally, and were subsequently assessed for their ability to localize sound in the horizontal plane. The unilaterally implanted animals were unable to perform this task, regardless of the duration of deafness. Among animals with BiCIs, early-onset hearing loss was associated with poor auditory localization performance, compared with late-onset hearing loss. However, performance in the early-deafened group with BiCIs improved significantly after multisensory training with interleaved auditory and visual stimuli. We demonstrate a possible neural substrate for this by showing a training-induced improvement in the responsiveness of auditory cortical neurons and in their sensitivity to interaural level differences, the principal localization cue available to BiCI users. Importantly, our behavioral and physiological evidence demonstrates a facilitative role for vision in restoring auditory spatial processing following potential cross-modal reorganization. These findings support investigation of a similar training paradigm in human CI users.